Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Wardah - Kurniasih Kurniasih; Ria Nofita Praptiwi; Rayhan Gunaningrat (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
In the cosmetics and facial care market, competition is increasingly competitive. Due to the large number of cosmetic products available in the market, a person's interest in buying something and their decision to make a purchase are influenced. Cosmetics have dangerous side effects for the body because of the chemical content. Researchers chose Wardah products as research targets because Wardah guarantees their quality by using high quality materials, has a halal label, and has halal laws. Wardah is made with natural, high quality and safe ingredients so as to avoid dangerous side effects for the skin and body. The purpose of the study is to ascertain how purchasing decisions are influenced by product quality and price. This study used a quantitative approach as its methodology. The study's findings demonstrate that product quality and price have a favorable and substantial impact on consumers' decisions to buy.